Tissue distribution of hepatopoietin-A: a heparin-binding polypeptide growth factor for hepatocytes. - Zarnegar, R (1990)
Hepatopoietin-A (HPTA) is a heparin-binding polypeptide growth factor which consists of a heavy and a light polypeptide chain with molecular weights of 70,000 and 35,000, respectively. It stimulates DNA synthesis in primary cultures of normal rat hepatocytes in serum-free medium. The complete purification and characterization of HPTA from rabbit serum were reported by us elsewhere. Recently we have determined the amino-terminal amino acid sequence of the rabbit HPTA light chain up to 24 residues and have shown that the sequence is not homologous with other known sequences. [N.B. Human hepatocyte growth factor, recently sequenced by two other groups, is the same molecular species as HPTA.] In the present paper we report the production of a neutralizing polyclonal antiserum raised in chicken against purified rabbit HPTA. This antiserum does not inhibit the mitogenic effect of other potent inducers of hepatocyte DNA synthesis (epidermal growth factor or acidic fibroblast growth factor), nor does it interact with these growth factors in an enzyme-linked immunosorbent assay (ELISA). The antibody recognizes HPTA, as was determined by Western immunoblotting. Since the tissue origin of HPTA is not known, this anti-HPTA antiserum was used to investigate the tissue distribution of HPTA in rabbits by immunohistostaining methods. Acinar cells of the pancreas, neurons of the brain, C cells of the thyroid, ductal cells of the salivary glands, and Brunners glands of the duodenum stained with anti-HPTA antibody. Liver, spleen, thymus, and kidney do not seem to contain appreciable amounts of HPTA. We confirmed these findings by extracting and purifying active HPTA from the stained tissues listed above. The anti-HPTA antibody recognizes HPTA purified from different tissues, as was determined by ELISA, Western immunoblotting, and immunoneutralization experiments.